Development and evaluation of the recombinant BP26 protein-based C-ELISA for human brucellosis diagnosis - Xie, Yujia; Lin, Shaoqing; Guo, Liping; Qi, Xinru; Zhao, Shiqi; Pei, Qichuan; Chen, Yixiao; Wu, Qi; Wang, Yun; Yao, Meixue; Yin, Dehui (Frontiers in Microbiology, 2025)
IntroductionTimely and accurate diagnosis is crucial for the effective treatment and prevention of brucellosis. Current serological diagnostics, primarily based on lipopolysaccharide (LPS), suffer from cross-reactivity with other Gram-negative bacteria, which limits their specificity. Periplasmic protein 26 (BP26), a highly immunogenic antigen found in Brucella, has emerged as a promising alternative for enhancing diagnostic specificity. This study aimed to develop and evaluate a competitive enzyme-linked immunosorbent assay (C-ELISA) utilizing monoclonal antibodies against BP26 for the diagnosis of human brucellosis, thereby providing a more accurate and specific diagnostic approach.MethodsThe study produced monoclonal antibody (mAb) against the BP26 protein through traditional mouse hybridoma technology and developed the C-ELISA method, and compared with a C-ELISA method based on LPS mAb. The detection performance was validated through the analysis of 190 human serum samples, which included 95 brucellosis serum samples and 95 negative serum samples collected by the Xuzhou Center for Disease Control and Prevention, and a comparative analysis was conducted on the diagnostic efficacy of indirect ELISA for brucellosis using both BP26 and LPS-based methods.ResultsThe BP26 mAb based C-ELISA achieved 100% sensitivity and specificity in detecting human brucellosis, significantly outperforming the C-ELISA based LPS mAb. Furthermore, the accuracy of the indirect enzyme-linked immunosorbent assay (I-ELISA) using BP26 protein was 98.95%, compared to an accuracy of LPS diagnosis was 99.47%. These results indicated that the BP26 mAb can effectively and accurately detected human brucellosis infections.ConclusionThis study successfully developed and evaluated a BP26 protein-based C-ELISA method for diagnosing human brucellosis, establishing a foundation for identifying alternative diagnostic antigens for brucellosis.